Computer Tomography Radiomics-Based Nomogram in the Survival Prediction for Brain Metastases From Non-Small Cell Lung Cancer Underwent Whole Brain Radiotherapy - Zhang, Ji; Jin, Juebin; Ai, Yao; Zhu, Kecheng; Xiao, Chengjian; Xie, Congying; Jin, Xiance (Frontiers in Oncology, 2021)
Prognostic parameters and models were believed to be helpful in improving the treatment outcome for patients with brain metastasis (BM). The purpose of this study to investigate the feasibilityof computed tomography (CT) radiomics based nomogram to predict the survival of patients with BM from non-small cell lung cancer (NSCLC) treated by whole brain radiotherapy (WBRT). A total of 195 patients with BM from NSCLC underwent WBRT from January 2012 to December 2016 were retrospectively reviewed.Radiomics features were extracted and selected from pretherapeutic CT images with least absolute shrinkage and selection operator (LASSO) regression. A nomogram was developed and evaluated by integrating radiomics features and clinical factors to predict the survival of individual patient. Five radiomics features were screened out from 105 radiomics features according to the LASSO Cox regression. According to the optimal cutoff value of radiomics score (Rad-score), patients were stratified into low-risk (Rad-score <= -0.14) and high-risk (Rad-score > -0.14) groups. Multivariable analysis indicated thatsex, karnofsky performance score (KPS) and Rad-score were independent predictors for overall survival (OS). The concordance index (C-index) of nomogram in training cohort and validation cohort were 0.726, 0.660, respectively. An area under curve (AUC) of 0.786 and 0.788 was achieved for the short-term and long-term survival prediction, respectively.In conclusion,the nomogram based on radiomics features from CT images and clinical factors was feasible to predict the OSof BM patients from NSCLC underwent WBRT.